1993
DOI: 10.3758/bf03337315
|View full text |Cite
|
Sign up to set email alerts
|

Radial-maze learning by lines of taste-aversion-prone and taste-aversion-resistant rats

Abstract: Lines of taste-aversion-prone and tas"te-aversion-resistant rats have been developed through 22 generations of bidirectional selective breeding for efficient or inefficient taste-aversion conditionability. The present study compared these two lines on food-reinforced foraging in a radialarm maze. The lines, although not identical on all measures taken, were equally adept at learning the maze. This finding supports prior indications that selective breeding has exerted an effect on learning that is highly specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Elkins et al (1992) observed that the selectively bred taste aversion prone (TAP) rats displayed a stronger ethanol-induced CTA response than taste aversion resistant (TAR) rats, despite the fact that ethanol CTA response was not a condition for selection. The TAP and TAR lines display similar abilities in other general learning paradigms, such as radial arm maze and bar pressing for food (Hobbs et al 1993;Orr et al 1997Orr et al , 2004.…”
Section: Discussionmentioning
confidence: 93%
“…Elkins et al (1992) observed that the selectively bred taste aversion prone (TAP) rats displayed a stronger ethanol-induced CTA response than taste aversion resistant (TAR) rats, despite the fact that ethanol CTA response was not a condition for selection. The TAP and TAR lines display similar abilities in other general learning paradigms, such as radial arm maze and bar pressing for food (Hobbs et al 1993;Orr et al 1997Orr et al , 2004.…”
Section: Discussionmentioning
confidence: 93%
“…This hypothesis is supported by results of studies that have shown rats selectively bred for high CTA (taste aversion-prone rats) to the emetic agent, cyclophosphamide, demonstrate greater CTA to a wide variety of pharmacological agents, including alcohol (Elkins et al, 1992), and demonstrate decreased consumption and preference for alcohol than do their counterparts selectively bred for low CTA (taste aversionresistant rats) (Orr et al, 1997). Notably, these lines do not differ in other learning tasks that involve a motivational component, which indicates that the line differences in CTA sensitivity are not due to differences in general learning ability (Elkins, 1986;Hobbs and Elkins, 1983;Hobbs et al, 1993). It might be useful to test this hypothesis in HAP and LAP mice to determine whether the observed line differences in CTA are specific to alcohol or perhaps reflect differences in a general susceptibility to acquire CTA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Elkins, Walters, and Orr 160 (see also Elkins 161 ) selectively bred animals from a population of Sprague–Dawley rats that developed either strong (taste aversion prone [TAP]) or weak (taste aversion resistant [TAR]) cyclophosphamide‐induced aversions. In later investigations, TAP and TAR rats were examined for differences in behaviors, such as rotation‐induced CTAs, ethanol‐induced loss of righting reflex and CTA, and radial arm maze learning, 160,162,163 to determine what other behaviors possibly correlated with an increased or decreased sensitivity to develop cyclophosphamide‐induced CTAs. Interestingly, these strains did not show reliable differences in standard learning preparations, such as the radial arm maze and bar pressing for food pellets, but they did show differences in cocaine‐ and ethanol‐induced CTAs, with TAP rats displaying more robust aversions with both of these drugs 160,164 .…”
Section: Relationship Between Self‐administration and Ctamentioning
confidence: 99%